2015
DOI: 10.1002/path.4467
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts predict poor outcome and promote periostin‐dependent invasion in oesophageal adenocarcinoma

Abstract: Interactions between cancer cells and cancer-associated fibroblasts (CAFs) play an important role in tumour development and progression. In this study we investigated the functional role of CAFs in oesophageal adenocarcinoma (EAC). We used immunochemistry to analyse a cohort of 183 EAC patients for CAF markers related to disease mortality. We characterized CAFs and normal oesophageal fibroblasts (NOFs) using western blotting, immunofluorescence and gel contraction. Transwell assays, 3D organotypic culture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(197 citation statements)
references
References 52 publications
10
182
2
3
Order By: Relevance
“…At the same time, periostin was reported to bind as a ligand to αvβ3 and αvβ5 integrins ( Fig. 1), thus signaling via the PI3K-Akt pathway within oesophageal adenocarcinoma cells; this indicated that periostin accumulated to a higher degree in ESCC tissue than in adjacent tissue outside the tumor (15).…”
Section: Periostin In Esophageal Cancermentioning
confidence: 95%
“…At the same time, periostin was reported to bind as a ligand to αvβ3 and αvβ5 integrins ( Fig. 1), thus signaling via the PI3K-Akt pathway within oesophageal adenocarcinoma cells; this indicated that periostin accumulated to a higher degree in ESCC tissue than in adjacent tissue outside the tumor (15).…”
Section: Periostin In Esophageal Cancermentioning
confidence: 95%
“…Pathologically, periostin has also been localized in infarcted myocardium Oka et al 2007), fibrosis (Okamoto et al 2011;Ishikawa et al 2014;Naik et al 2012;Takayama et al 2006;Uchida et al 2012), tissues undergoing wound healing (Nishiyama et al 2011;Norris et al 2007;Ontsuka et al 2012;Zhou et al 2010), and cancer-associated stroma (Fukushima et al 2008;Kashima et al 2009;Kikuchi et al 2008Kikuchi et al , 2014Liu et al 2014;Nitsche et al 2016;Oskarsson and Massague 2012;Qin et al 2016;Ruan et al 2009;Sung et al 2016;Tian et al 2015;Underwood et al 2015;Wang and Ouyang 2012). Taken together, periostin expression is well correlated with tissue regeneration (Conway et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Activated CAFs specifically upregulate the expression of α-SMA, fibroblast-specific protein 1 (FSP-1/S100A4), NG2, platelet-derived growth factor receptor (PDGFR)-α/β [13], fibroblast activation protein (FAP) [14], uPA [15], periostin [16], tenascin-C (TN-C) [17], palladin [18], podoplanin [19], and natriuretic peptide B (NPPB) [5]. There also exist evidences that some molecules are specifically downregulated in CAFs, such as caveolin-1 [20] and laminin [21], while epithelial cell markers (cytokeratin) and endothelial cell markers (CD31) disappear.…”
Section: The Biomarkers Of Cafsmentioning
confidence: 99%